Slowing down of 100 keV antiprotons in Al foils - K. Nordlund (Results in Physics, 2018)
Using energy degrading foils to slow down antiprotons is of interest for producing antihydrogen atoms. I consider here the slowing down of 100 keV antiprotons, that will be produced in the ELENA storage ring under construction at CERN, to energies below 10 keV. At these low energies, they are suitable for efficient antihydrogen production. I simulate the antihydrogen motion and slowing down in Al foils using a recently developed molecular dynamics approach. The results show that the optimal Al foil thickness for slowing down the antiprotons to below 5 keV is 910 nm, and to below 10 keV is 840 nm. Also the lateral spreading of the transmitted antiprotons is reported and the uncertainties discussed. Keywords: Antiprotons, Stopping power, Slowing down, Molecular dynamics